Tumor inchado de Pott e empiema epidural em paciente pediátrico - Galstyan-Minasova, Vicky; Alamar-Velazquez, Agustín; Ibañez-Alcañiz, Isabel; Lesmas-Navarro, Maria José; Armengot-Carceller , Miguel (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2024)
We report a case of a 12-year-old adolescent diagnosed with Pott’s puffy tumor (PPT) and epidural empyema as a complication of acute rhinosinusitis. PPT is described as an inflammation in the frontal region due to the formation of a subperiotic abscess and osteomyelitis of the frontal bone. Although uncommon nowadays, this entity usually appears in adolescents, and it is frequently associated with intracranial complications. Early diagnosis, antibiotic therapy and endoscopic treatment when required are essential to avoid the risk of intracranial progression.